Optimization of Cellulase Production by Aspergillus niger ITBCC L74 with Bagasse as Substrate using Response Surface Methodology - Abdullah Abdullah; Hamid Hamid; Marcelinus Christwardana; H. Hadiyanto (Bogor Agricultural University, Indonesia, 2018)
Cellulase is a very important enzyme for lignocelluloses based ethanol production. Bagasse contains mainly cellulose (57.76%), hemicellulose (12.44%), lignin (21.34%), and others (7.96%). Lignocellulosic material has been considered as the good option for cellulase production because it is cheap and already available in a huge amount. The objective of this research was to produce cellulase enzyme and to optimize it by using response surface methodology. The bagasse with water content of 80% was incubated with 2 ml inoculum of Aspergillus niger ITBCC L74 in a 250 ml Erlenmeyer flask. After reaching the specified time the enzyme was extracted and then determined for its activity. Effect of process parameters such as pH, urea and MgCl2 addition were studied. The optimal cellulase activity was achieved at urea concentration of 4.5% (w/w), MgCl2 concentration of 1 mM and pH of 3.5, with maximum enzyme activity was 0.630 U/gr.